2013
DOI: 10.1007/s13139-013-0221-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Uptake Pattern of Bone Scintigraphy in Patients with Hepatocellular Carcinoma Following Treatment with High-Intensity Focused Ultrasound

Abstract: Purpose This study retrospectively reviews the characteristic bone scintigraphic findings in 18 patients with hepatocellular carcinoma (HCC) following treatment with high-intensity focused ultrasound (HIFU). A potential complication of HIFU is damage to the tissues along the path of the ultrasound beam and structures superficial to the lesion of interest. Methods Patients with hepatocellular carcinoma who underwent a bone scan between 1st December 2005 and 31st December 2011 were considered for this study. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…Dans tous les cas, ces atteintes osseuses ne modifient heureusement pas le pronostic des leucémies aigues chez l'enfant [ 14 ]. Il est enfin utile de rappeler que des hypofixations sur une scintigraphie du squelette peuvent être en rapport avec certaines tumeurs bénignes (hémangiome [ 15 ]), des métastases (thyroïde, rein, neuroblastome [ 5 , 16 , 17 ]), certains traitements anticancéreux notamment la radiothérapie et le traitement par les ultrasons (hypofixations costales chez des patients atteints hépatocarcinomes [ 18 ]), une infection osseuse [ 5 ], ou bien rester dans de rares cas sans cause décelable [ 19 ].…”
Section: Discussionunclassified
“…Dans tous les cas, ces atteintes osseuses ne modifient heureusement pas le pronostic des leucémies aigues chez l'enfant [ 14 ]. Il est enfin utile de rappeler que des hypofixations sur une scintigraphie du squelette peuvent être en rapport avec certaines tumeurs bénignes (hémangiome [ 15 ]), des métastases (thyroïde, rein, neuroblastome [ 5 , 16 , 17 ]), certains traitements anticancéreux notamment la radiothérapie et le traitement par les ultrasons (hypofixations costales chez des patients atteints hépatocarcinomes [ 18 ]), une infection osseuse [ 5 ], ou bien rester dans de rares cas sans cause décelable [ 19 ].…”
Section: Discussionunclassified
“…Combining functional SPECT images with high-resolution morphologic CT scans, osteonecrosis can be well evaluated, which has been shown in a SPECT/CT study about femoral head osteonecrosis by Motomura et al [ 22 ]. Another study by Ma et al [ 38 ] showed that tissue ablation using high-intensity focused ultrasound ultimately led to osteonecrosis, which could be visualized by photopenic areas surrounded by an increased tracer region on planar scintigraphic images [ 20 , 39 ]. The mechanism was based on a rapid temperature increase, which is comparable to cement hardening.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is consistent with this report, showing increased SPECT/CT activity in a lengthy period of time, although the general impression was a decrease in the mean uptake ratio with time. This increased activity can most likely be attributed to bone remodeling after surgical fracture treatment [ 38 ].…”
Section: Discussionmentioning
confidence: 99%